Formulasi Sediaan Sabun Cair Ekstrak Daun Ramania (Bouea macrophylla Griffith) sebagai Antiseptik - Mahdi, Nur; Rezekiah, Rezekiah; Ani, Agustina (Sinteza, 2024)
Ramania leaves (Bouea macrophylla Griffith) are natural ingredients that have activity as an antiseptic. Ramania leaves contain flavonoids, alkaloids, steroids and tannins. This study aims to make antiseptic liquid soap from ramania leaf extract with a concentration of 5%, 10%, 15%. This study used experimental methods in the laboratory. three formulations were made (FI, FII, FIII with a concentration of 5%, 10%, 15%). Evaluation includes organoleptic, homogeneity, pH, specific gravity, foam height. Antiseptic test was carried out using the zigzag method. he antiseptic test was carried out using the replica method. The statistical test for evaluating preparations is One Way Anova, for antiseptic testing using Paired sample t-test. The results of several evaluations have met the requirements, except that the specific gravity does not meet the SNI criteria. The antiseptic test is indicated by the percentage of bacterial reduction. The percentage of bacterial reduction in FI, II, and III respectively was 40.5; 48.5; and 57.5%. It can be seen that increasing the extract concentration can reduce the number of bacterial colonies. The results of the One Way Anova statistical test (a = 0.05) showed that there was no difference in the results of the preparation evaluation, the results of the paired sample test (a = 0.05) showed a significant difference in the antiseptic test. Based on the results of research on the specific gravity test however all formulas do not meet the criteria. In the antiseptic test, all formulas were effective in inhibiting bacterial growth.